KADAR KOLESTEROL DARAH PADA PENDERITA OBESITAS DI KELURAHAN KORPRI SAMBIROTO SEMARANG - Andri Sukeksi; Herlisa Anggraini (JURNAL KESEHATAN, 2009)
Abstract Patients with obesity have excessive fat accumulation in the body, causes the occurrence of obesity is usually caused by an abnormal eating pattern that is eaten in the number of very large and eat at night.. Obese People hove elevated levels of cholesterol in the body (hypercholesterolemia) (Mangku Sitepoe, l993). Cholesterol is a form of at that is naturally present in foods derived from animals, which allows the human body to make sex hormones and sexual function, adrenal hormones are necessary in the process of metabolism, and vitamin D. (lmam Suharto, 2004). Cholesterol is also useful for transporting fat in the blood throughout the body, which in a long time that blood vessels may be narrowed or closed. If the arteries (arteries) that provide blood to the hear, brain or organs - covered other important organs, can lead to risk of atherosclerosis, heart attack, stroke or failure of other vital organ functions. High levels of cholesterol called hypercholesterolemia is closely associated with the disease of obesity. (Corine T. Netzer, 1994). Based on the above background raised The question, "How can blood cholesterol levels in obese people in the housing KORPRI Sambiroto Semarang Kelurahan". The purpose of this study are: Measuring the value of Body Mass Index (BMD to determine the criteria for obesity, Measuring cholesterol in people with obesity. Knowing the influence of obesity on cholesterol levels Method: This type of research study is a descriptive The entire study population was obese in the housing KORPRI Sambiroto Semarang Kelurahan. Study sample was obese at 8 RW Semarang Kelurahan sambiroto taken in totol population. From the results of examination and discussion of research on the cholesterol wells in obese Semarang Kelurahan Simongan Ngemplak can be summarized as follows: From the samples that have been carried out Inspection lowest cholesterol 156.4 mg / dl, the highest cholesterol 256.8 mg / dl, cholesterol levels an Average of 197.4 mg / dl. From the results obtained based on Body Mass Index (BMI) that was not always obese, high cholesterol levels, because cholesterol is not always influenced by obesity, but more affected on the consumption of foods containing cholesterol. Like eating meat, jerohan, and eggs that can enhance the increase in blood cholesterol levels, because the meat in the diet, jerohan, and cholesterol content of eggs is high enough.   K keywords : obesity, cholesterol